Studi Literatur: Strategi Reading Habit Sebagai Upaya Optimalisasi Literasi - Faizah, Alif (BASICA, 2023)
This research study aims to determine the strategy of implementing "Reading Habit" in improving literacy skills in Madrasah Ibtidaiyah students seen from the role of parents and teachers, as well as the relationship between the application of "Reading Habit" to literacy skills in Madrasah Ibtidayah Students. The method taken uses a literature study approach, with reference to previous research relevant to the strategy of implementing reading habit programs in improving literacy skills in students. This research shows that education in today's era, the interest needed in students in supporting education is the interest in reading. Reading activities will affect insight into knowledge and literacy skills in students. But in fact, Indonesian students are less fond of reading, and cause Indonesia to be low in the reading category compared to other countries. So it needs to be applied to elementary school and Madrasah Ibtidaiyah students related to the reading habit program. The strategy in implementing this habituation can be assisted through the role of parents and teachers, so that the benefits of realizing the application of this reading habituation can improve reading skills by thinking critically in understanding problems, as well as literacy skills in elementary school and madrasah ibtidaiyah students